SISTEM PEMILU ONLINE BERBASIS PROTOKOL TWO CENTRAL FACILITIES - Sikki, Muhammad Ilyas (JREC (Journal of Electrical and Electronics), 2013)
An election is an simple example of a scenario where security and confidentiality of data between partiesis critical. General election system that used in Indonesia as it long still use conventional trick thatevokes a lot of problem as elector of double, voice distension and another fault and also long time forvote count. This conventional trick also require big costs and resources. To settle that thing, one ofsolution which can be done is use electronic voting ( e-voting ) with arrange general election systemonline that building to use a safe protocol.System that is made has default pock secure votingreguirements to get settles and secure security each threat which will happen. One of protocol which canaccomplish partly criterion default secure voting reguirements and has security zoom that passably isTwo Central Facilities Protocol , where consisting of Central Legitimazation Agency (CLA) for electorvalidation and Central Tabulating Facility (CTF) for vote count.Keywords : General election system, e-voting, Two Central Facilities, Central Legitimazation Agency,Central Tabulating Facility.